Momentum Investment Strategies across Time and Trends: A Review and Preview - Karki, Dipendra; Khadka, Prajjwol Bikram (Nepal Journal of Multidisciplinary Research, 2024)
Background: This study provides a bibliometric analysis of momentum investment strategies, examining their historical evolution, behavioral dynamics, and the challenges faced by professionals in equity markets. It aims to explore the persistent profitability of momentum strategies amidst market fluctuations and the significant influence of behavioral biases on trading decisions. Methods: Employing a Bibliometric Analytical framework, the study systematically maps the knowledge structure of momentum investment strategies. It utilizes the Dimensions database for scholarly journal searches and examines peer-reviewed research publications spanning from 1993 to 2024. This method enables the identification of key research works, emerging trends, and an assessment of the literature's impact. Results: The research reveals the persistent profitability of momentum strategies despite market changes, highlighting the significant role of behavioral biases in trading decisions. This work contributes to both academic discourse and practical investment strategy development, offering insights into exploiting momentum's transformative potential in dynamic equity markets. Conclusion: This study contributes to both academic discourse and practical investment strategy development by offering evidence-based insights into the effectiveness of momentum strategies. It identifies research gaps, suggests new directions for future studies, and analyzes collaboration networks to enhance interdisciplinary research efforts. Novelty: The utilization of a Bibliometric Analytical framework in studying momentum investment strategies brings a novel approach to the field. This method not only offers a systematic mapping of knowledge but also facilitates the identification of influential research works and emerging trends, guiding both academic research and practical applications.